(untitled) (Journal of Atomic and Molecular Sciences, 2021)
The theoretical model, developed by Khare, has been modified to calculate the total cross sections for K-shell ionization of 12 atom targets (C, N, O, Al, Fe, Se, Ag, Sb, Ho, Au, Bi, U) due to electron impact at incident electron energy from ionization threshold to 1 GeV. The various calculated cross sections are in remarkable agreement with available experimental data and other theoretical cross sections.